Memaknai Kebijakan Program Makan Bergizi Gratis (MBG) Berdasarkan Teori Hierarki Kebutuhan Maslow di Sd Negeri 2 Kendari Sulawesi Tenggara Tahun 2025 - Julia Lambe; Hartati Bahar; Agnes Mersatika Hartoyo (Inovasi Kesehatan Global, 2026)
The Ministry of Health and the Coordinating Ministry for Human Development and Culture indicate that 41% of students experience hunger, which has an impact on the decline in the quality of education. The Free Nutritional Meals (MBG) policy is present as a strategy oriented towards more inclusive and sustainable education. The purpose of this study is to determine the Free Nutritional Meals (MBG) program policy based on Maslow's Hierarchy of Needs Theory at SD Negeri 2 Kendari, Southeast Sulawesi in 2025. This study is a qualitative study with a phenomenological approach. Informants in this study numbered 10 people, namely 3 key informants and 7 supporting informants selected using a purposive sampling technique. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results of the study on students' physiological needs show variations in the level of students' satiety. Students' need for safety shows students are calmer and more focused, although there are still variations in perceptions among some students and parents. The need for socialization shows that the MBG program encourages communication, as well as the formation of attitudes of mutual assistance and mutual cooperation. The need for appreciation shows equal conditions regardless of economic background. The need for self-actualization shows increased participation, discipline, and responsibility, although influenced by individual character. It can be concluded that the MBG program has been able to fulfill the physiological, security, socialization, appreciation and self-actualization needs of students, although some needs are influenced by individual character.